Unwillingness to Organ Donation and Religious Concerns in Turkey - Zeynep Burcu Uğur (İnsan & Toplum)
This study aimed to determine the Turkish population’s attitudes towards organ donation in comparison to European countries and discuss religious concerns regarding organ donation. Public attitudes were studied using the Eurobarometer 72.3 survey which is the most recent survey on organ donation in Europe and is population representative. Among 1,004 respondents from Turkey, over 50% of participants were not willing to donate their organs, and around 16% of people remain equivocal. Only about 19% of respondents were familiar with the national laws regarding organ donation, and the most (35.7%) commonly cited reason for refused organ donation was: “religious reasons”. In Turkish socio-cultural context, an essential component for success in organ donation is addressing religious concerns. As the crux of the organ donation is acceptance of ‘brain death’ as formal death, and Turkish Presidency’s guidelines on organ donation do not clarify whether brain death is accepted as death or not, Islamic scholars in Turkey needs to discuss brain death and clarify its permissibility.